2023
DOI: 10.1039/d2sm01190e
|View full text |Cite
|
Sign up to set email alerts
|

A textile-reinforced composite vascular graft that modulates macrophage polarization and enhances endothelial cell migration, adhesion and proliferation in vitro

Abstract: At the present time, there is no successful off-the-shelf small-caliber vascular graft (<6 mm) for the repair or bypass of the coronary or carotid arteries. In this study, we...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…Although the integrin binding sites within the GelMA hydrogel were observed to support M2 polarization, we found that GelMA hydrogel did not induce an M2 phenotype in 2D cell culture . A more potent induction method of M2 macrophages is by following the interleukin 4 (IL-4) signaling pathway .…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Although the integrin binding sites within the GelMA hydrogel were observed to support M2 polarization, we found that GelMA hydrogel did not induce an M2 phenotype in 2D cell culture . A more potent induction method of M2 macrophages is by following the interleukin 4 (IL-4) signaling pathway .…”
Section: Introductionmentioning
confidence: 96%
“…6 Although the integrin binding sites within the GelMA hydrogel were observed to support M2 polarization, 5 we found that GelMA hydrogel did not induce an M2 phenotype in 2D cell culture . 7 A more potent induction method of M2 macrophages is by following the interleukin 4 (IL-4) signaling pathway. 8 Delivering IL-4 from a tissue engineering scaffold is a potential way to promote an M2 macrophage response from the scaffold material and to facilitate tissue regeneration.…”
Section: Introductionmentioning
confidence: 99%